Self-transcend, anxiety and depression in cancer patients receiving treatment. Barquisimeto. 2015 - Jesús Manuel Guerrero Alcedo; Abigail Ramses Prepo Serrano; José Gregorio Loyo Álvarez (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: many investigations have determined the existence of psychopathological illnesses like anxiety and depression before, during, and after the disease process for cancer patients. Objective: to determine the relation between Self-Transcend, Anxiety and Depression in cancer patients receiving treatment. As well as, to establish differences based on gender. Materials and Methods: association, transversal study executed between December 2014 and April 2015. The sample was made up of 140 cancer patients who receive chemotherapy and/or radiotherapy treatment with a minimum of one month in treatment, 62 men and 78 women between the ages of 18-60, who attended four health centers in the state of Lara-Venezuela. Each participant gave their consent and responded voluntarily to Reed's Self-transcendence Scale, the Adult Manifest Anxiety Scale, and Zung's Depression Scale. Results: using Pearson's correlational analysis, a small negative relation was found between Self-Transcend and the dimension Social Concerns/Stress of the Anxiety scale (r=-.235; p<.01) as well as, a moderate negative relation with Depression (r=-.439; p<.01). As for Anxiety and Depression, a moderate positive relation was found (r=.519; p<.01). Student's T study showed significant differences for Anxiety and the dimensions of Worry/Oversensitivity and Physiological Anxiety.  Conclusion: the results of this study manifest the need for interventions that potentiate self-transcendence in cancer patients, with the purpose of mitigating the symptoms associated with both disorders.  Key words: spirituality, anxiety, depression, chemotherapy, radiotherapy, cancer.